The Role of Internal M&A Teams in Takeovers - Aktas, Nihat; Boone, Audra; Witkowski, Alexander; Xu, Guosong; Yurtoglu, Burcin (Review of Finance, 2021)
This article provides insights into the inner workings of internal corporate M&A teams using survey evidence from sixty-five firms from Austria, Germany, and Switzerland. We find that internal teams create value, especially relative to external advisors, by directing transaction rationales, screening targets, and employing performance metrics to assess post-merger success. Teams emphasizing economic rationales as a merger motive are associated with higher returns than those teams more apt to consider behavioral motives. We consider several team characteristics and find that financial experience is the most persistent and significant attribute in explaining the outcomes across various deal stages. Another key result from our survey-based evidence is that latent M&A team factors explain ∼54% of the acquirer fixed effects in announcement return regressions.